(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article discusses the factors for developing the autopedagogical competence of a future teacher and the design of a plan for conducting research work in stages in accordance with the proposed scientific ideas, as a result of the formation and development of autopedagogical competence of the future teacher, it is stated that it is possible to determine and study the impact of the main psycho-physiological and social determinants on all structural and functional components of the development of autopedagogical competence and the mechanisms of interaction between them.